1998
DOI: 10.1074/jbc.273.6.3718
|View full text |Cite
|
Sign up to set email alerts
|

Conformation-dependent Antibacterial Activity of the Naturally Occurring Human Peptide LL-37

Abstract: The influence of ion composition, pH, and peptide concentration on the conformation and activity of the 37-residue human antibacterial peptide LL-37 has been studied. At micromolar concentration in water, LL-37 exhibits a circular dichroism spectrum consistent with a disordered structure. The addition of 15 mM HCO 3 ؊ , SO 4 2؊ , or CF 3 CO 2 ؊ causes the peptide to adopt a helical structure, with approximately equal efficiency, while 160 mM Cl ؊ is less efficient. A cooperative transition from disordered to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

58
601
6
3

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 586 publications
(671 citation statements)
references
References 35 publications
58
601
6
3
Order By: Relevance
“…The majority of the experiments were carried out using LL-37-U, synthetic LL-37 with a sequence identical to the biologically active form and no isotopic labels. CD spectroscopy was used to confirm that this synthetic peptide behaved as reported previously in the literature (18,19,25,26), exhibiting a random coil structure in pure water and a primarily helical signature in the presence of anions or lipids at micromolar peptide concentrations (data not shown). A second sample of LL-37, LL-37-L, was synthesized incorporating site-specific isotopic labels: 15 NVal 21 , 13 CdO-Leu 31 , and 13 C R -Ala 13 .…”
Section: Resultssupporting
confidence: 68%
See 3 more Smart Citations
“…The majority of the experiments were carried out using LL-37-U, synthetic LL-37 with a sequence identical to the biologically active form and no isotopic labels. CD spectroscopy was used to confirm that this synthetic peptide behaved as reported previously in the literature (18,19,25,26), exhibiting a random coil structure in pure water and a primarily helical signature in the presence of anions or lipids at micromolar peptide concentrations (data not shown). A second sample of LL-37, LL-37-L, was synthesized incorporating site-specific isotopic labels: 15 NVal 21 , 13 CdO-Leu 31 , and 13 C R -Ala 13 .…”
Section: Resultssupporting
confidence: 68%
“…Oriented DMPC bilayers were also directly hydrated with tris buffer ( Figure 8B) to test whether the presence of ions, known to affect the structure and aggregation state of LL-37 in solution (18), also affect its interaction with lipids. For DMPC with 0% or 1% LL-37, the 31 P spectra obtained with either hydration method are identical ( Figure 8A,B) indicating that these samples are insensitive to low salt concentrations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was early recognized that LL-37 and LL-37 analogs have direct effects on eukaryotic cells. Johansson and colleagues (28) observed an increased fluorescein staining by fluorescein diacetate of human peripheral leukocytes and the T-cell line MOLT after incubation with LL-37 at concentrations of approximately 100 mg ml À1 . They concluded that LL-37 is toxic not only to bacteria but also to eukaryotic cells.…”
Section: Discussionmentioning
confidence: 99%